Operational details of the 2008 fertilizer subsidy in Ghana: Preliminary report - Banful, Afua Branoah (International Food Policy Research Institute, 2009)
In July 2008, the government of Ghana instituted a country-wide subsidy on 50Kg bags of four types of fertilizer in an effort to mitigate the effect of rising energy and food prices. Farmers received the subsidy in the form of fertilizer- and region-specific vouchers distributed by agricultural extension agents. This descriptive report details the operational design of the subsidy program and offers preliminary observations of its implementation. The fertilizer subsidy was a unique example of a public-private partnership in which thegovernment consulted heavily with fertilizer importers in the design stage and relied exclusively on the existing private distribution system to deliver fertilizer to farmers. While this structure offers clear benefits, initial observations suggest scope for improvement in both the system design and implementation. Poor timing, shortage of fertilizer and a small network of fertilizer retailers participating in the program prevented fertilizer use from increasing as much as was possible within the program budget and may have disadvantaged smaller retailers. Amidst such constraints, less than 50 percent of the vouchers country-wide had been redeemed by the end of the planting seasons.